2015
DOI: 10.1088/1367-2630/17/8/083032
|View full text |Cite
|
Sign up to set email alerts
|

Mixing of ${0}^{+}$ and ${0}^{-}$ observed in the hyperfine and Zeeman structure of ultracold ${\mathrm{Rb}}_{2}$ molecules

Abstract: We study the combination of the hyperfine and Zeeman structure in the spin-orbit coupled A b u u 1 3 Σ Π − + complex of Rb 87 2 . For this purpose, absorption spectroscopy at a magnetic field around B 1000= G is carried out. We drive optical dipole transitions from the lowest rotational state of an ultracold Feshbach molecule to various vibrational levels with 0 + symmetry of the A b − complex. In contrast to previous measurements with rotationally excited alkali-dimers, we do not observe equal spacings of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…The linewidth of the photoassociation dip is 15 MHz, close to the natural linewidth of about 10 MHz. The next photoassociation line is expected 570 GHz away (29).…”
mentioning
confidence: 91%
“…The linewidth of the photoassociation dip is 15 MHz, close to the natural linewidth of about 10 MHz. The next photoassociation line is expected 570 GHz away (29).…”
mentioning
confidence: 91%
“…In 87 Rb 2 [21] it has been shown that the coupling between Ω = 0 + and Ω = 0 − states can induce an unusually large hyperfine structure of several hundreds of MHz. Thus we examined the possibility for a similar pattern in NaRb.…”
Section: Hyperfine Structure Of the Excited Levelsmentioning
confidence: 99%
“…The molecules are irradiated for a duration of a few milliseconds by a cw grating-stabilized diode laser which resonantly excites them to c 3 Σ + g levels, leading to molecular loss. We measure the remaining number of molecules by first dissociating them into ultracold atom pairs and then measuring the corresponding atom number via absorption imaging (for details see [19,23]). By scanning the laser frequency from shot to shot, a resonance spectrum is recorded [see Fig.2b) to d)].…”
Section: B Photoexcitation Spectroscopymentioning
confidence: 99%